A Flexible Software-Defined Networking-Based Privacy-Preserving Method for Internet of Things-Based Smart City Environment Based on the Neighbors Situation - Fernandez-Campusano, C (IEEE Computer Society, 2025)
We introduce “DPSmartCity,” a context-aware dynamic software-defined networking (SDN) framework that preserves privacy in smart cities. Enhancing the Internet of Things (IoT)-centric infrastructure with dynamic network management, the SDN controller employs contextual information and trust evaluation, determining secure routes from IoT devices to the cloud. © 1970-2012 IEEE.